2016
DOI: 10.5114/fn.2016.60364
|View full text |Cite
|
Sign up to set email alerts
|

The topography of cortical microbleeds in frontotemporal lobar degeneration: a post-mortem 7.0-tesla magnetic resonance study

Abstract: IntroductionFrontotemporal lobar degeneration (FTLD) is a heterogeneous disorder with various clinical and histological subtypes [22]. FTLD is the second most common cause of presenile dementia with different genetic subtypes [20]. Despite the fact that most cases have a presenile onset, FTLD is not rare amongst elderly patients [3]. A recent neuropathological study showed that age together with vascular and Alzheimer-related co-pathology contributes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…21,22 Also the presence of cortical microbleeds are linked to the degenerative process (23). However, some recent MRI studies show that WMCs are more distributed than the grey matter lesions, suggesting two separate types of neurodegenerative pathology in FTLD.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Also the presence of cortical microbleeds are linked to the degenerative process (23). However, some recent MRI studies show that WMCs are more distributed than the grey matter lesions, suggesting two separate types of neurodegenerative pathology in FTLD.…”
Section: Discussionmentioning
confidence: 99%
“…Microbleeds are currently not known to be causative or reactionary to the conditions of ALS. Studies have linked cortical microbleeds (CMBs) with Alzheimer's disease [92, 93] and shown that CMBs, while rare in frontotemporal lobar degeneration, are increased in the regions affected by neurodegenerative lesions. This suggests that the progression of Alzheimer's disease promotes CMBs.…”
Section: Microbleedsmentioning
confidence: 99%
“…Relationships between CMBs and other neurodegenerative and neuroinflammatory pathologies have also been hypothesized, 10,38 although they have not been directly confirmed in neuropathology. Therefore, it cannot be excluded that the investigation of further pathological hallmarks could inform us on the genesis of these lesions.…”
Section: Discussionmentioning
confidence: 99%